Título Padrão - Moraes, Margarete Farias de (Informação em Pauta, 2021)
Although medical records are very old and have a long history of evolution, it was only in the 20th century that medical records were the object of specific knowledge treatment. Register the cases and assistance and then discuss them; learning and using these records has enabled the health sciences to develop and advance. The management of health records and information identifies a link as a fundamental practice for access, scientific advancement and governance of the health system. This article aims to analyze the importance of classifying medical records and health information with the case in the ICD, in addition to presenting the basic result techniques.